Pengaruh Literasi Keuangan dan Gaya Hidup Terhadap Minat Menabung Mahasiswa Fakultas Ekonomi Universitas Negeri Medan - Br. Sidebang, Tamaria; Fahrani, Meutia; Situmorang, Eva; Hasyim, Hasyim (Innovative: Journal Of Social Science Research, 2024)
The purpose of this study was to see how financial literacy and lifestyle of students at the Faculty of Economics, State University of Medan affect their interest in saving. A survey was conducted on 30 students of Economic Education, Faculty of Economics used to collect data using quantitative methods. Data analysis was carried out using the SPSS program for multiple linear regression. The results showed that financial literacy has a positive and significant impact on interest in saving (t-count 3.370> t-table 1.703; sig. 0.002). Lifestyle also has a positive impact on interest in saving, but this impact is not statistically significant (t-count 2.467> t-table 1.703; sig. 0.064). Simultaneously, financial literacy and lifestyle both have a significant impact on interest in saving. The coefficient of determination (R2) of 0.368 indicates that financial literacy and 36.8% of the variation in interest in saving students' finances to encourage them to save, and the importance of managing their lifestyle so as not to stop them from saving.